Emerging Trends of Radicalization in Global Context and Pakistan and their Solution in the Light of Islamic Teachings (International Research Journal on Islamic Studies (IRJIS), 2022)
Terrorists use violence to create fear. Comprehending why terrorists kill innocent civilians is crucial to understanding the situation. The current discussion on ‘root causes' focuses on identifying a terrorist's anti-civilization motivations. But the debate over what motivates a terrorist misses the circumstances that enable terrorism. To reduce the number of terrorists, it is vital to identify their enablers and root causes. Terrorism's purpose will take a decade or more to decrease, and its capabilities will need continual attention. Radicalism shares several values. It was a happy, tranquil, prosperous period. Fundamentalists believe that change comes from above, and hence support force and coercion above democracy and popular will. So, the structure isn't democratic. One for every fanatical. Armed forces toppled progressive anti-imperialist leader Ahmed Soekarno in 1964, slaughtering communists posing as American imperialism. In 1973, General Pinochet killed Chile's first elected socialist president, Silva Durlande. Forcing martial rule in Pakistan and deposing Zulfiqar Ali Bhutto, fundamentalists supported General Zia-ul-Haq. Extremism and fanaticism yield their fruit. Our religious seminaries teach the same mindset that is spread by Islamic groups and religious politicians, which has produced the present position for Islam and Muslims worldwide. However, what is the right Islam? If there is a religious riot in Muslim culture, it is not the preaching of secularism, but a religious counter narrative that may bring peace. ?Keywords: Radicalization, Emerging trends, Solution, Islam, Pakistan
Keywords: Redicalization; Emerging trends; Solution; Islam; Pakistan